Projetos e Cloud Computing: uma análise dos fatores críticos de sucesso relevantes para o sucesso de projetos - Correia, Silvia Regina Veronese (2020)
The use of cloud computing technology has become common in information technology (IT) departments of organizations. Investments to migrate classic infrastructures to this technology have increased and, with this, many IT projects have been structured considering its use. Cloud computing allows organizations to manage the amount of resources needed at the time they need them, with lower cost of resources and faster implementations and can thereby reduce the cost and time of projects. However, it brings some challenges for project management such as: teams, access restrictions, shared environments, specific technical knowledge, contract and change management. These factors can influence the success of these projects. Thus, this study aims to answer the following research question: what are the critical success factors (CSF) for projects that use cloud computing technology? The methodology used was an exploratory qualitative study, through in-depth interviews and structured questions. The main theoretical contribution is the increase in the current literature that permeates the themes critical success factors, cloud computing and projects, demonstrating the important CSF for the success of cloud computing projects. This study demonstrated that the CSF with greater relevance for cloud projects is the technical capacity of the team, followed by the support of top management and soft skills of the team. In addition, this study demonstrated that contract item management is an important factor for cloud projects. In terms of practical contribution, this study provides guidance to project managers regarding the critical factors needed to drive projects of this type to success.